Analisis Pendapatan Usahatani Ubi Jalar (Ipomea batatas) dan Keragaan Penyuluhan Pada Kelompok Tani Hurip di Cikarawang, Dramaga, Bogor - Masithoh, Siti; Novita, Ita; Widara, Derina Astuti (JURNAL AGRIBISAINS, 2017)
This study was aimed at assessing the extension activities conducted in Hurip Farmer Group, Cikarawang Village, Dramaga District, Bogor Regency. It was also done to assess farmers’ income level and extension performa.  A descriptive analysis was used.  Respondents were farmers aged 26-60 years. They had various education and farming experience levels. They had elementary school education with 3-20 years farming experience, junior high school education with 5-10 farming experience, and senior high school education with 3-20 years farming experience.  The average income gained by these farmers was Rp 9,850,000/1 ha with an income over cash cost of Rp5,675,000/1 ha. The R/C over cash cost value in this sweet potato farming business was 1.72 indicating that this business was profitable and feasible.  It was concluded that extension activities in Hurip Farmert Group was done well and farmers’ income improvement-oriented. Key words: extension. farmer income, sweet potatoes